A Survey of U.S. Obstetrician‐Gynecologists' Clinical and Epidemiological Knowledge of Cryptosporidiosis in Pregnancy. (4th October 2013) - Domjahn, B. T.; Hlavsa, M. C.; Anderson, B.; Schulkin, J.; Leon, J.; Jones, J. L.
Summary: Although cryptosporidiosis is frequently diagnosed in the U.S., there has been very little assessment of obstetrician–gynaecologist knowledge about this disease. In 2010, we surveyed U.S. obstetricians about the diagnosis, treatment and epidemiology of cryptosporidiosis. Data were examined through univariable analysis and multivariable regression models. Of 1000 obstetrician–gynaecologists surveyed, 431 (43.1%) responded. Only 44.4% of respondents correctly identified that prolonged, intermittent diarrhoea would lead them to consider cryptosporidiosis in a differential diagnosis. Routine ova and parasites (O&P) testing was incorrectly chosen to identify Cryptosporidium in stool by 30.4% of respondents. Questions about nitazoxanide, the only drug approved by the U.S. Food & Drug Administration (FDA) for treatment of cryptosporidiosis, were the most frequently missed questions. Only 9.0% of respondents correctly classified nitazoxanide as an FDA pregnancy Category B drug, and only 5.6% of respondents correctly indicated that FDA approved nitazoxanide for immunocompetent patients aged ≥1 years. Regarding prevention‐ and control‐related knowledge, only 14.1% of respondents correctly indicated that alcohol‐based hand sanitizers were not effective at inactivating Cryptosporidium spp., and <10% correctly indicated that cryptosporidiosis is a reportable disease in their state of practice. Multivariable analysis found that ≥19 years in practice was positively associated with O&P diagnostic testing knowledge, while rural and urban non‐inner city practice location, compared with suburban practice location, was positively associated with nitazoxanide knowledge. The low level of knowledge among obstetrician–gynaecologists about cryptosporidiosis indicates a need to develop resources for physicians about all aspects of cryptosporidiosis, particularly on diagnosis, treatment and prevention strategies.